Writing for CBC Wartime Radio Drama: John Weinzweig, Socialism, and the Twelve-Tone Dilemma - Sumner, Carolyne (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2016)
Radio drama was a quintessential source of entertainment for Canadian audiences during the Second World War, and the Canadian Broadcasting Corporation (CBC) used the art form to distribute propaganda and garner support for the Canadian war effort. Similarly, CBC radio drama became an essential artistic outlet for artists and composers to articulate their political beliefs to a national audience. This article frames Canadian composer John Weinzweig’s works for the CBC radio drama series New Homes for Old (1941) within the socio-political climate of the 1930s and 1940s and suggests that radio drama provided Weinzweig with a national soapbox for his radical socialist ideals during a time of political upheaval.My research draws on archival materials from Library and Archives Canada, the CBC Music Library Archives, and Concordia’s Centre for Broadcasting and Journalism Studies to build upon the biographical work of Elaine Keillor and Brian Cherney. I establish Weinzweig’s socialist ties and argue that his political leanings prompted him to simplify his serial language in favour of a simplified modernist aesthetic, which appealed to Canada’s conservative wartime audiences. This study of Weinzweig’s radio works reveals how the composer desired to make serial compositions accessible and palatable, and shows how he incorporated vernacular idioms such as folk songs and national anthems as foils to the elitist European serial aesthetic. In doing so, I show how Weinzweig uses a powerful and pervasive medium to promote his unique compositional style and also to reflect the cultural, political, and aesthetic ideals of leftist socialism.